Simulation of Stress-Strain State of Shovel Rotary Support Kingpin; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Khoreshok A. A. Aleksey Alekseevich; Buyankin P. V.; Vorobyev A. V. Aleksey Vasilievich; Dronov A. A. Anton Anatolievich (2016, 2016)
Title screen